Entre o mar e estrela, um lugar para se bem viver : a problemática da expansão urbana da Cidade de Baía Formosa/RN - Lima, Carlos José Cavalcanti de (2004)
The urban expansion problem of Baía Formosa, a southern edge city of de Rio Grande do Norte eastern coast, which has been presented in other coast Brazilian towns, specially on those with tourist activities increase. Therefore, this situation brings huge concerns to their inhabitants, to their technical /scientific community and to the governments, because of the conflicts of interest and of the growth of urban problems that this has been created. At Baía Formosa, the situation is aggravated because the city is confined, once around it, there are large private proprieties, environmental preservation area and the sea, at the eastern edge. The objectives of this study are the analyses of this city expansion process in order to obtain adequate alternatives and defining methodology to apply in other urban nucleus that are subjected to similar situations. Of course, presents social relations, environmental conditions and promoting local population insertion should be considered in order that enjoin this process and contributing to a better social balance. This case study has used bibliography research, field data, maps and soil occupation recorders and photographs of the area, besides the primary data gathering by surveys carried out with many social actors. The present analysis shows that the urban expansion observed today is featured by a recent unsustainable model, which attacks the environment and brings either farm conflicts. On the other hand, the ecological tourism can represent an alternative in order to achieve an adequate expansion form, without forgetting the several structural parameters necessary to support the sustainable activities